Research on strength properties of geopolymer based on tungsten mine waste and recycled ground glass - Szymon Dawczyński; Paulina Cieśla; Marcin Górski; Rafał Krzywoń (Instituto Politécnico de Viseu, 2019)
Introduction: Geopolymers are the modern inorganic materials obtained as a result of chemical reaction under strongly alkaline conditions. The main advantages of these materials are: high strength parameters, fire resistance, frost resistance and resistance to aggressive environment. Because of lower CO2 emission during production process, they are also considered as environmentally friendly materials in comparison to ordinary Portland cement (OPC) systems. Objectives: The aim of the investigation was to define the impact of recycled ground glass addition on mechanical properties of geopolymeric binder made from tungsten mine waste. Methods: The strength parameters of geopolymeric samples were determined on the basis of three-point flexural test and uniaxial compression test. Results: The geopolymer samples that contain 20%, 40% and 80% of recycled ground glass present similar flexural strength. The compressive strength of glass-based geopolymers increases with growing content of recycled ground glass. Conclusions: In terms of flexural strength, the most favourable composition was the mixture composed of 60% recycled ground glass and 40% tungsten mine waste. In terms of compressive strength, the most favourable composition was the mixture composed of 80% recycled ground glass and 20% tungsten mine waste.